Valuation Of Pt. Alamtri Resources Indonesia (“Adro”) And Financial Feasibility Study Of Mentarang Hydroelectric Power Plant - Irvan Rahadian Ilham; Erman Arif Sumirat; Subiakto Soekarno (Journal Research of Social Science, Economics, and Management, 2025)
Adaro Andalan Indonesia (“AADI”) divestment, determine its company valuation, assess the financial implications of Mentarang Hydroelectric Power Plant, and to propose strategies for future value optimization. This study employed a mix of qualitative (SWOT and PESTEL) and quantitative (Financial statement analysis, financial ratio analysis, financial modelling using Discounted Cash Flow (DCF) financial feasibility study, with relying on secondary data. Post-AADI divestment, ADRO experienced a significant decline in assets. Liabilities, and equity. Despite this, ADRO maintains a strong liquidity, high profitability, and low leverage within the industry. Result shows that ADRO is still undervalued from the relative and absolute valuation. By the relative valuation using the EV/EBITDA the implied share price is Rp6.124 and using the Unlevered Cash Flow (UCF) method, the valuation of ADRO ranges from Rp 2.988 to Rp4.405. Mentarang Hydroelectric Power Plant shows a profitable project based on the optimistic scenario with a 8 cents/kWh for 30 years contract. In conclusion, ADRO is well positioned for future growth due to the development and increasing demand in global aluminium market and investments in green business. The divestment of its thermal coal energy is seen as a strategic move towards a more sustainable business in the future,